The impact of different ovarian stimulation protocols on the expression levels of GDF-9 and BMP-15 in cumulus cells of follicles - Cheng, Lili; Zhang, Jie; Li, Dongxiu; Xu, Pengyu; Liu, Shan; Guo, Ruijuan; Wang, Xue; Zhang, Li (Frontiers in Endocrinology, 2025)
ObjectiveTo analyze the expression levels of the oocyte-secreted factors growth differentiation factor-9 (GDF-9) and bone morphogenetic protein-15 (BMP-15) in cumulus cells (CCs) under different controlled ovarian stimulation (COS) protocols and their association with oocyte maturity and embryo developmental potential.MethodsThis study included 76 patients requiring intracytoplasmic sperm injection (ICSI) due to severe oligoasthenoteratozoospermia or previous ICSI treatment, resulting in the collection of 749 CC samples. Patients were divided into four groups based on COS protocols: short-acting luteal phase (14 patients, 168 CCs), long-acting follicular phase (21 patients, 189 CCs), micro-stimulation (12 patients, 86 CCs) and antagonist (29 patients, 306 CCs). The mRNA was extracted from cumulus granulosa cells, and the relative levels of GDF-9 and BMP-15 were measured using real-time quantitative PCR (Q-PCR). The expression levels of GDF-9 and BMP-15 were compared across different ovarian stimulation protocols, while oocyte maturation, fertilization, cleavage, and blastocyst formation were assessed. The expression levels of GDF-9 and BMP-15 were compared across protocols, and oocyte maturation, fertilization, cleavage and blastocyst formation were assessed.ResultsGDF-9 and BMP-15 levels were substantially higher in MII oocytes than in MI and GV oocytes and were also elevated in the normal fertilization group, high-quality cleavage embryos and high-quality blastocysts. Growth differentiation factor-9 expression was higher in the short-acting luteal phase protocol than in the antagonist protocol, whereas BMP-15 expression was higher in both the short-acting luteal phase and long-acting follicular phase protocols compared with the micro-stimulation and antagonist groups.ConclusionGDF-9 and BMP-15 are reliable indicators of oocyte developmental potential. The long-acting follicular phase and short-acting luteal phase protocols enhance oocyte maturity and embryo development, whereas the micro-stimulation and antagonist protocols appear less favorable.